A novel cell-based assay for dynamically detecting neutrophil extracellular traps-induced lung epithelial injuries - Lv, Dandan; Xu, Yiming; Cheng, Hongqiang; Ke, Yuehai; Zhang, Xue; Ying, Kejing (Experimental cell research, 2020)
Acute lung injury (ALI) and its more severe form, acute respiratory distress syndrome (ARDS) are common lung disorders characterized by alveolar-capillary barrier disruption and dyspnea, which can cause substantial morbidity and mortality. Currently, a cluster of acute respiratory illnesses, known as novel coronavirus (2019-nCoV)-infected pneumonia (NCIP), which allegedly originally occurred in Wuhan, China, has increased rapidly worldwide. The critically ill patients with ARDS have high mortality in subjects with comorbidities. Previously, the excessive recruitment and activation of neutrophils (polymorphonuclear leukocytes [PMNs]), accompanied by neutrophil extracellular traps (NETs) formation were reported being implicated in the pathogenesis of ALI/ARDS. However, the direct visualization of lung epithelial injuries caused by NETs, and the qualitative and quantitative evaluations of this damage are still lacking. Additionally, those already reported methods are limited for their neglect of the pathological role exerted by NETs and focusing only on the morphological features of NETosis. Therefore, we established a cell-based assay for detecting NETs during lung epithelial cells-neutrophils co-culture using the xCELLigence system, a recognized real-time, dynamic, label-free, sensitive, and high-throughput apparatus. Our results demonstrated that lung epithelial injuries, reflected by declines in cell index (CI) values, could be induced by lipopolysaccharide (LPS)-activated PMNs, or NETs in a time and dose-dependent manner. NETs generation was verified to be the major contributor to the cytotoxicity of activated PMNs; protein components of NETs were the prevailing cytotoxic mediators. Moreover, this cell-based assay identified that PMNs from severe pneumonia patients had a high NETs formative potential. Additionally, acetylsalicylic acid (ASA) and acetaminophen (APAP) were discovered alleviating NETs formation. Thus, this study not only presents a new methodology for detecting the pathophysiologic role of NETs but also lays down a foundation for exploring therapeutic interventions in an effort to cure ALI/ARDS in the clinical setting of severe pneumonia, including the emerging of NCIP. •A real-time, dynamical and label-free assay for detecting NETs is established using the xCELLigence system.•This establishment relies on the co-culture of lung epithelia and neutrophils, focusing on evaluating NETs’ effects.•This cell-based assay has feasibility and practicality in clinical applications.•This methodology builds a solid foundation for exploring therapies for ALI/ARDS, including the emerging NCIP.